Penerapan Metode Six Sigma pada IKM Manufaktur Industri Pendukung (Supporting Industry) untuk Meminimalkan Jumlah Produk Cacat - Cucu Wahyudin; Agung Apriliandi (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2021)
Supporting industry is industries that make goods and services, sell to the free market, or to other industries to support their final products with greater value. With characteristics being business to business, the efficiency of the production process is the key. An efficient production process can minimize defects so that production costs can be minimized. This research is an application of the six sigma method in supporting industries that produce educational aids. Was conducted in a company with a defect rate of up to 8,10%, named combination mirror products with a sigma value is 3,71. Process improvement by implementing the DMAIC (Define-Measure-Analyze-Improve-Control). At the define stage, the dominant defect is the Shrink Mark defect, which is 31% of all types of product defects. The cause of defect is the absence of parameter setting values ​​that are used consistently on the injection molding machine. Through experiments, this research determines the parameter setting values ​​that can minimize shrink mark type defects. The selected parameter setting factors are Cooling Time and Holding Pressure with a value of 20 seconds and Holding Pressure of 105 MPa. The reject rate of the combination mirror product was successfully minimized and the sigma value increased to 4.13.